PENGARUH HYGIENE PENGOLAHAN MAKANAN TERHADAP KUALITAS MAKANAN DI HOTEL ASTON RASUNA JAKARTA - Anisatul Auliya; Dinda Nira Aprilia (Jurnal Hospitality dan Pariwisata, 2017)
To produce the good quality of foods and drinks, health and demanded by costumers,the food and beverage staff must be concerned to apply the hygiene in foodprocessing during making the products. This study uses a quantitative method withthe number of respondents as many as 30 people, they are employees of the hotelAston Rasuna Jakarta. Instruments in this study using a Likert scale questionnaireform with a 1-5 score. This analysis technique using multiple linear regression theresults show that the hygiene of food processing affects to the quality of food. It canbe seen from the test results that have been done using SPSS version 20.The results of regression tests show that variable Personal Hygiene (X1), foodhygiene (X2), Hygiene Equipment (X3) and Hygiene Kitchen (X4) produce F countequal to 3.436 with α amounting to 0,023. Which if F count> F table (2.76) withsignificantly below 0.05, it indicates that the Personal Hygiene (X1), food hygiene(X2), Hygiene Equipment (X3) and Hygiene Kitchen (X4), an influence on the qualityof the food (Y).Keywords : hygiene in food processing, food quality